1966
DOI: 10.1126/science.151.3715.1226
|View full text |Cite
|
Sign up to set email alerts
|

Osteolytic Sterol in Human Breast Cancer

Abstract: Eleven of twelve human breast cancers contained a lipid which increased urinary (45)Ca and (40)Ca excretion of (45)Ca-labeled, parathyroidectomized rats receiving a low Ca diet. The lipid has mobility on thin-layer chromatography and gas-liquid chromatography close to, but not identical with, that of 7-dehydrocholesterol. Authentic 7-dehydrocholesterol has osteolytic activity similar to that of the extracted sterol. Fluorescence and Lieberman-Burchard reactions of the extracted sterol are similar to those of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1968
1968
1980
1980

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Destruction of bone by osteolytic métastasés is the usual explanation for the hyper calcemia of breast cancer. G o rd a n et al [9] have demonstrated osteolytic sterols in tumor extracts and plasma of the patients with osseous métastasés, and these sterols have shown to be derivatives of sitosterol and sigmasterol [10]. It is of interest that hypocalcemia has been reported in a small number of cases with osteoblastic métastasés [15].…”
Section: Discussionmentioning
confidence: 99%
“…Destruction of bone by osteolytic métastasés is the usual explanation for the hyper calcemia of breast cancer. G o rd a n et al [9] have demonstrated osteolytic sterols in tumor extracts and plasma of the patients with osseous métastasés, and these sterols have shown to be derivatives of sitosterol and sigmasterol [10]. It is of interest that hypocalcemia has been reported in a small number of cases with osteoblastic métastasés [15].…”
Section: Discussionmentioning
confidence: 99%
“…In period 11 (83 days) the patient was given a formula diet containing 40% of calories as corn oil in which 9-sitosterol-22,23-5H had been incorporated during its manufacture; each day the patient ingested 620 mg of 13-sitosterol of specific activity 74,245 dpm/mg. On the 2nd day of this regimen radioactivity was detected in the plasma; it rose to reach a constant level of approximately 1000 dpm/ml plasma in about 2 wk (Fig.…”
Section: Calculationsmentioning
confidence: 99%
“…Some tumours, those of the breast in particular, are capable of produc ing sterols which cause osteolysis, thus promoting hypercalcaemia. Gordan et al [5] have demonstrated the activity of these sterols on bones of rats which had previously been parathyroidectomized. True anti-tumour activity of mithramycin may result in an inhibition of these sterols, and thus prevent osteolysis.…”
Section: Discussionmentioning
confidence: 99%